Plasmid-mediated antibiotic resistance gene transfer under environmental stresses: Insights from laboratory-based studies - Li, Li-Guan; Zhang, Tong (The Science of the total environment, 2023)
Although clinical settings play a major role in the current global dissemination of antibiotic resistance, once antibiotic resistance bacteria and genes are released into the environment, their fate will be subject to complex ecological processes. One of the processes prevalent in microbial communities – horizontal gene transfer – can largely facilitate the dissemination of antibiotic resistance genes (ARGs) across phylogenetic and ecological boundaries. Especially, plasmid transfer has aroused increasing concern as it has been proved a significant role in promoting ARG dissemination. As a multi-step process, plasmid transfer can be influenced by various factors, among which those stresses caused by environmental pollutants are important elements affecting the plasmid mediated ARG transfer in the environment. In fact, diverse traditional and emerging pollutants are continuously entering the environment nowadays, as evidenced by the global occurrence of pollutants like metals and pharmaceuticals in aquatic and terrestrial systems. It is therefore imperative to understand to what extent and in which way the plasmid mediated ARG dissemination can be influenced by these stresses. Over the past decades, numerous research endeavours have been made to understand the plasmid mediated ARG transfer under various environmental relevant pressures. In this review, progress and challenges of studies on environmental stress regulating plasmid mediated ARG dissemination will be discussed, with specific focus on emerging pollutants like antibiotics and non-antibiotic pharmaceuticals, metals and their nanoparticles, disinfectants and disinfection by-products, as well as the emerging particulate matter like microplastics. Despite the previous efforts, we are still lacking insights into the in situ plasmid transfer under environmental stresses, which can be addressed by future studies considering environmental relevant pollution status and multi-species microbial communities. We believe that future development of standardized high-throughput screening platforms will assist in rapidly identifying which pollutants enhance plasmid transfer and also which ones may block such gene transfer processes. [Display omitted] •Traditional and emerging pollutants potentially facilitate plasmid transfer.•Existing studies hardly reflect plasmid transfer in the environment.•Microbial community and pollutant concentration are key factors for experimental studies.